Taxonomy of advanced access practice profiles among family physicians, nurse practitioners and nurses in university-affiliated team-based primary healthcare clinics in Quebec - Arnaud Duhoux; Catherine Hudon; France Légare; Isabelle Vedel; Isabelle Gaboury; Djamal Berbiche; Mylaine Breton; Sabina Abou Malham; Lara Maillet; Nadia Deville-Stoetzel; Nassera Touati (BMJ Open)
Objectives The advanced access model is highly recommended to improve timely access to primary healthcare (PHC). However, its adoption varies among PHC providers. We aim to identify the advanced access profiles of PHC providers.Design A cross-sectional study was conducted between October 2019 and March 2020. Latent class analysis (LCA) measures were used to identify PHC provider profiles based on 14 variables, 2 organisational context characteristics (clinical size and geographical area) and 12 advanced access strategies.Setting and participants All family physicians, nurse practitioners and nurses working in the 49 university-affiliated team-based PHC clinics in Quebec, Canada, were invited, of which 35 participated.Primary outcome measure The LCA was based on 335 respondents. We determined the optimal number of profiles using statistical criteria (Akaike information criterion, Bayesian information criterion) and qualitatively named each of the six advanced access profiles.Results (1) Low supply and demand planification (25%) was characterised by the smallest proportion of strategies used to balance supply and demand. (2) Reactive interprofessional collaboration (25%) was characterised by high collaboration and long opening periods for appointment scheduling. (3) Structured interprofessional collaboration (19%) was characterised by high use of interprofessional team meetings. (4) Small urban delegating practices (13%) was exclusively composed of family physicians and characterised by task delegation to other PHC providers on the team. (5) Comprehensive practices in urban settings (13%) was characterised by including as many services as possible on each visit. (6) Rural agility (4%) was characterised by the highest uptake of advanced access strategies based on flexibility, including adjusting the schedule to demand and having a large number of open-slot appointments available in the next 48 hours.Conclusion The different patterns of advanced access strategy adoption confirm the need for training to be tailored to individuals, categories of PHC providers and contexts.